Legal Problems in the Conversion of Agricultural Land to Housing (Case Study of Pringgabaya District) - kin, Khaerurozikin (Journal of Law, Politic and Humanities, 2025)
The conversion of agricultural land into housing has become commonplace among business actors. This condition has prompted the government to issue regulations through the Coordinating Ministry for Economic Affairs of the Republic of Indonesia, which addresses the control of the conversion of protected rice fields, known as Protected Rice Fields (LSD). The LSD regulation is a new policy issued in 2020, referring to Presidential Regulation Number 59 of 2019 concerning the Control of Rice Field Conversion. The purpose of this regulation is to minimize the use of rice fields for residential and industrial areas, which is one of the causes of the decline in the availability of rice raw materials. This study aims to analyze the dynamics of agricultural land conversion in the context of the LSD regulation and its impact on regional development, particularly in the housing sector. The research method used is a descriptive qualitative approach by collecting data through literature studies, regulations, and policy analysis. The results of the study show that although the LSD regulation aims to maintain national food security, its implementation in the field faces various challenges, including limited coordination between institutions, local economic interests, and the growing need for infrastructure and public housing development. This policy also creates a dilemma between protecting agricultural land and accelerating regional development. Therefore, synergy between the central government, regional governments, and business actors is needed so that land conversion control can be carried out sustainably without hampering economic growth and regional development.